Effect of nitrogen, phosphorus and potassium fertilization on the yield of broccoli cultivars (2018)
One of the causes of overusing compound and simple fertilizers in “Oriente Antioqueño” region is the low offer of research articles on fertilization in broccoli. Two experiments were carried out atmunicipality of Rionegro, Antioquia (Colombia). The first experiment was conducted in the second semester of 2013 in which two broccolis cultivars, Compact and De Cicco, were used. A randomizedcomplete block design (RCBD) with four nitrogen doses (0, 50, 90 and 130 kg N ha-1) was arranged in a factorial 2 x 4, getting eight treatments. Using “San Cristobal” model in a RCBD design, Avengerand Legacy cultivars were grown in the second semester of 2014 including four levels of N, P2O5 and K2O as factors, arranging a total of 12 treatments in an incomplete factorial. Results of this experiment showed that in the first test, Compact cultivar reached a maximum production of 15.5 t ha-1 and De Cicco developed non-tradable inflorescences where a dose of 90 kg N ha-1 was applied, showing a low adaptation to this environmental conditions. In the second experiment, the relative growth height rates –stem diameter and yields- did not show significant statistical differences (P0.05) regarding the treatments and cultivars evaluated. Avenger and Legacy got the highest yields, 19.0 and 12.2 t N ha-1 respectively, using doses of 60 kg N ha-1, 40 kg P2O5 ha-1 and 55 kg K2O ha-1.